A study on awareness of pharmacoeconomics among post graduates in a tertiary care teaching hospital - Jayasree, D.; Uppu, Bharathi; Devi, B. Vasundhara (International Journal of Research in Medical Sciences, 2016)
Background: Pharmacoeconomics identifies, measures, and compares the costs and consequences of drug therapy to healthcare systems and society. At present health care cost is increasing day by day. Especially poor and middle class people unable to bear the cost of medical expenses. This is the doctor responsibility to balance both cost and quality of treatment. Methods : For this study 100 postgraduates of various departments were enrolled in Sri Venkateswara Medical College. We gave a questionnaire on pharmacoeconomics which contains four parts. This questionnaire describes awareness, knowledge, application and students’ attitude about pharmacoeconomics. Results: The willingness to participate in the study among postgraduates was extremely poor. Only 30% of post graduates have awareness of pharmacoeconomics. 28% of postgraduate students were having Knowledge on pharmacoeconomics and 16% on application of pharmacoeconomics.65% of postgraduates showed interest to know about pharmacoeconomics. 55% of postgraduates felt pharmacoeconomics should include in postgraduate curriculum. 75% of postgraduates wanted to conduct continuous medical education on pharmacoeconomics. Only 11% showed self interest in learning pharmacoeconomics. 21% of postgraduates agreed that need a specialization degree for pharmacoeconomics. Conclusion: By conducting this study we concluded that postgraduates have extremely poor awareness and knowledge. They don’t know the importance of pharmacoeconomics. Right from their medical education it’s necessary to include in MBBS curriculum, conducting CME and work shop on pharmacoeconomics will enhance their interest and application of pharmacoeconomics in their medical practices.